Overall Success Factors Affecting the Performances of Hybrid Cloud ERP: A Case Study of Automobile Industries in Thailand - Eampoonga, Itthiphol; Leelasantitham, Adisorn (Journal of Mobile Multimedia, 2023)
The hybrid cloud ERP system is widely used in automobile companies in Thailand. It is a popular and effective strategic tool that aids in boosting organization’s competitiveness. However, because of their complexity, high risk, high resource requirements, and high investment costs, ERP projects still have a significant failure rate. It is widely acknowledged by academics and practitioners alike to be an extremely challenging endeavour. This study proposes a conceptual paradigm for postmodern ERP implementation across the entire life cycle. Mixed methodologies for this model’s theoretical development included case study observation, literature review, semi-structured interviews with ten IT experts and ERP consultants, and online questionnaires. Based on information gathered from 455 system users from 114 automobile industries sector, it was analysed by using Structural Equation Modelling (SEM). For data analysis, the partial least squares (PLS) method was employed. Out of the eighteen (18) hypotheses, fifteen (15) were supported by the PLS-SEM results. The conceptual model from the study that was presented can be put to use or helpful in the organization’s management, or project managers can utilize it as a framework and direction for hybrid cloud ERP implementation. The findings of the study can also be used to create a conceptual framework for the actual use of ERP systems for automobile industry, such as the incorporation of blockchain and postmodern ERP systems in many sectors of business. There is discussion of the findings’ implications for practical and research, and potential study areas are proposed.